Sintren as a Traditional Performing Art in Mirat Village - Kartika, Nyai; Reiza D. Dienaputra; Susi Machdalena; Awaludin Nugraha; Agus S. Suryadimulya; Susi Yuliawati; Sriwardani, Nani (Mudra Jurnal Seni Budaya, 2024)
Sintren art is a traditional art that developed in almost all coastal areas of the island of Java. In Majalengka, sintren art developed in Mirat Village, Leuwimunding District. Sintren as a traditional art grew among rural communities that were becoming modern so sintren then survived as a traditional performing art that had an influence on the social life of the community. This research was carried out using qualitative research methods which are believed to be a scalpel in research so as to help explain the research object factually. Data collection techniques were carried out by direct observation and interviewing sources. The results of this research show that sintren in Mirat Village is not only a traditional art that was initially performed in ceremonies or rituals, but also a traditional performing art that can be performed during circumcision celebrations, weddings, and welcoming guests who come to the village. There has been a shift in sintren performances, currently sintren can be performed anytime and anywhere depending on the enthusiasm and demand of the community, because currently the values contained in this sintren performing art are no longer closely tied to a ceremony or ritual alone. Sintren art absorbs the cultural values of the community so Sintren performing arts have become part of the culture of the Mirat community.